Neural correlates of traumatic memories in posttraumatic stress disorder: a functional MRI investigation. - Lanius, Ruth A.; Williamson, Peter C.; Densmore, Maria (American Journal of Psychiatry, 2001)
|WbObjective:[|WB] The neuronal circuitry underlying posttraumatic stress disorder (PTSD) was studied in traumatized subjects with and without PTSD. |WbMethod:[|WB] Traumatized subjects with (N=9) and without (N=9) PTSD were studied by using the script-driven symptom provocation paradigm adapted to functional magnetic resonance imaging at a 4-T field strength. |WbResults:[|WB] PTSD subjects showed significantly less activation of the thalamus, the anterior cingulate gyrus (Brodmann's area 32), and the medial frontal gyrus (Brodmann's area 10/11) than did the comparison subjects. |WbConclusions:[|WB] The findings suggest anterior cingulate, frontal, and thalamic involvement in the neuronal circuitry underlying PTSD. Reprinted by permission of the publisher.